Trace element contamination in feather and tissue samples from Anna's hummingbirds. (September 2017) - Mikoni, Nicole A.; Poppenga, Robert; Ackerman, Joshua T.; Foley, Janet; Hazlehurst, Jenny; Purdin, Güthrum; Aston, Linda; Hargrave, Sabine; Jelks, Karen; Tell, Lisa A.
Abstract: Trace element contamination (17 elements; Be, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Mo, Cd, Ba, Hg, Tl, and Pb) of live (feather samples only) and deceased (feather and tissue samples) Anna's hummingbirds ( Calypte anna ) was evaluated. Samples were analyzed using inductively coupled plasma-mass spectrometry (ICP-MS; 17 elements) and atomic absorption spectrophotometry (Hg only). Mean plus one standard deviation (SD) was considered the benchmark, and concentrations above the mean + 1 SD were considered elevated above normal. Contour feathers were sampled from live birds of varying age, sex, and California locations. In order to reduce thermal impacts, minimal feathers were taken from live birds, therefore a novel method was developed for preparation of low mass feather samples for ICP-MS analysis. The study found that the novel feather preparation method enabled small mass feather samples to be analyzed for trace elements using ICP-MS. For feather samples from live birds, all trace elements, with the exception of beryllium, had concentrations above the mean + 1 SD. Important risk factors for elevated trace element concentrations in feathers of live birds were age for iron, zinc, and arsenic, and location for iron, manganese, zinc, and selenium. For samples from deceased birds, ICP-MS results from body and tail feathers were correlated for Fe, Zn, and Pb, and feather concentrations were correlated with renal (Fe, Zn, Pb) or hepatic (Hg) tissue concentrations. Results for AA spectrophotometry analyzed samples from deceased birds further supported the ICP-MS findings where a strong correlation between mercury concentrations in feather and tissue (pectoral muscle) samples was found. These study results support that sampling feathers from live free-ranging hummingbirds might be a useful, non-lethal sampling method for evaluating trace element exposure and provides a sampling alternative since their small body size limits traditional sampling of blood and tissues. The results from this study provide a benchmark for the distribution of trace element concentrations in feather and tissue samples from hummingbirds and suggests a reference mark for exceeding normal. Lastly, pollinating avian species are minimally represented in the literature as bioindicators for environmental trace element contamination. Given that trace elements can move through food chains by a variety of routes, our study indicates that hummingbirds are possible bioindicators of environmental trace element contamination.